Application of dynamic display technology to identify gaps after pulmonary vein isolation in catheter ablation of atrial fibrillation. Issue 1 (July 2022) - Chen, Wei-Tso; Lo, Li-Wei; Tsai, Wen-Chin; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chung, Fa-Po; Liao, Jo-Nan; Tuan, Ta-Chuan; Chao, Tze-Fan; Lin, Chin-Yu; Chang, Ting-Yung; et al.
Abstract: Background: The identification of post pulmonary vein isolation (PVI) gaps by activation and voltage maps is time-consuming. This study aimed to investigate the characteristics, efficiency and accuracy of LiveView dynamic display module (EnSite™ Dynamic Display; Abbott, Abbott Park, IL, USA) in unmasking post PVI gaps and conduction block line. Method: Twenty four patients with paroxysmal atrial fibrillation (PAF) who failed to achieve first-pass PVI or with recurrent PAF were enrolled. Ninety-six pulmonary veins (PVs) were evaluated, and gaps were identified in 25 (26.0%) PVs. The gap location was confirmed by activation and propagation maps; 110 frames on gaps and 118 frames on block lines were analyzed by using LiveView module. We defined isochronal crowding in the local activation time (LAT) mode as three colors between two adjacent electrodes. Each frame was classified as with or without isochronal crowding in LAT mode and one/continuous color or isochronal discontinuity in reentrant mode. The gray color inside the PVs was considered to represent conduction block. Result: The isochronal crowding could be found on both gap and block line in LAT mode, whereas isochronal discontinuity only presented on the block line in reentrant mode. The sensitivity and specificity of isochronal discontinuity or gray color in reentrant mode to identify block line were 61.0% and 100%, respectively. The sensitivity and specificity of isochronal crowding or gray color in LAT mode to identify block line were 71.2% and 71.8%, respectively. Conclusion: Reentrant mode in LiveView module is very specific in identifying block lines. We proposed an efficient, practical algorithm to differentiate the block line from PV gaps. Graphical abstract: Unlabelled Image Highlights: Pulmonary vein gaps and block lines present different dynamic activation patterns. The electrogram is usually fractionated on gaps but not on block lines. Using dynamic mapping and electrogram can identify pulmonary vein gaps efficiently.